Development of a small-scale reactor system for bioethanol production from agriculture waste geared towards small industries applications in Malaysia - Mohammad Omar, Abdullah; Lim, Soh Fong; S.F., Salleh; T. M., Tai; S. L., Leo; A. K., Umar (Development of Renewable Energies, Environment and Power Quality, 2011)
Bioethanol derived from agriculture can be an alternative fuel source to petroleum-based fuel as the fuel hike and supply depreciation. In Malaysia, agriculture waste materials especially from chip industries (such as banana/yam/tapioca) are potential to be one of the feedstock for producing bioethanol. The utilization of the waste feedstock for biofuel production does not disturb the food chain as it is a waste-to-energy concept based. This paper presents the development of an affordable reactor system that is feasible to be applying in Small and Medium Enterprise (SME) in Malaysia. The reactor system concentrated on the fermentation of the feedstock. Based on the experimental results, it is estimated that the yielding percentage of bioethanol is around 14 % for batch production. Moreover, it is estimated that this reactor is able to produce bioethanol around 0.85 L for each batch of production which implied a petrol fuel cost saving for SMEs around 10 % if bioethanol is blended with the fossil fuel.